Respon Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) terhadap Pemberian Paklobutrazol - Diah Karunia Binawati; Ngadiani Ngadiani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
This study aims to examine the response of cayenne pepper plants to the treatment of paklobutrazole with various concentrations. This study used a completely randomized design (CRD) with 6 treatment concentrations of paklobutrazole, namely: 0 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm, with 4 repetitions. The parameters observed were: plant height, flowering time, and the number of flowers of chili plants. Data analysis used Analysis of Variance (ANOVA) according to the experimental design at a significance of 0.5. The follow-up test used the BNT test at a level of 0.05 if there was a significant effect. The results showed that the administration of paclobutrazole with a concentration of 500 ppm gave a better effect on plant height, flowering time, and number of leaves compared to other treatments.